Implementation of Islamic Education Study Program Learning Based on Blended Learning in the Industrial Era 4.0 at IAIN Samarinda - Setiawan, Agus (Dinamika Ilmu, 2019)
The purpose of this study is to describe 1) how the implementation of blended learning at the State Islamic Institute of Samarinda (IAIN Samarinda), and 2) how students respond to the implementation of blended learning. The research subjects were students in the Islamic Religious Education program at Faculty of Tarbiyah and Teacher Training IAIN Samarinda East Kalimantan. The method used was a descriptive qualitative research approach. The technique used observation, interview, and questionnaire instruments. The subjects were 32 students of Islamic Religious Education Program at FTIK IAIN Samarinda. The data analysis was carried out with the model of Miles & Huberman, namely in three steps: data reduction, display and conclusion drawing. The results of this study indicated that 1) students and lecturers are actively involved in the face-to-face learning process and online activities on the e-learning website. These results indicated that a positive potential for education with blended learning innovation is implemented at public Islamic higher education such as IAIN Samarinda.